Metric properties of the "prescribe healthy life" screening questionnaire to detect healthy behaviors: a cross-sectional pilot study - Paola Bully; Alvaro Sanchez; Gonzalo Grandes; Haizea Pombo; Ma Soledad Arietalenizbeaskoa; Veronica Arce; Catalina Martinez; on behalf of the PVS Group (BMC, 2016)
Abstract Background Feasible and valid assessment of healthy behaviors is the first step for integrating health promotion in routine primary care. Therefore, the aim of this study was to develop and evaluate the validity and reliability of the "prescribe healthy life" screening questionnaire, a brief tool for detecting physical activity levels, consumption of fruit and vegetables, tobacco use and patients' compliance with minimal recommendations. Methods An observational cross-sectional study to determine the reliability and validity of this questionnaire by means of mixed (qualitative and quantitative) methods. Thirteen healthcare professionals designed the questionnaire. One hundred and twenty-six patients from three primary care health centers within Osakidetza (Basque Health Service, Spain) filled in the "Prescribe Healthy Life" Screening Questionnaire and completed an accelerometry record, the PREDIMED Food Frequency Questionnaire and a co-oximetry as gold standards for physical activity, dietary intake and tobacco use, respectively. Correlations, sensitivities, specificities, likelihood ratios and test-retest reliability were calculated. Additionally, the feasibility and utility of the questionnaire were evaluated. Results Both reliability and concurrent validity for the consumption of fruit and vegetables (rspearman = 0.59, rspearman = 0.50) and tobacco use (rspearman = 0.76, r = 0.69) as their overall performance in the detection of unhealthy diet (accuracy = 76.8%, LR + = 3.1 and LR- = 0.31) and smokers (accuracy = 86.8%, LR + = 6.1 and LR- = 0.05) were good. Meanwhile, the reproducibility (0.38), the correlation between the minutes of physical activity (0.34) and LR+ (1.00) for detection of physical activity were low. On average the questionnaire was considered by patients easy to understand, easy to fill in, short (5-6 min) and useful. Conclusion The "Prescribe Healthy Life" Screening Questionnaire, PVS-SQ, has proved to be a simple and practical tool for use in the actual context of primary care, with guarantees of validity and reliability for the diet and tobacco scales. However, the physical activity scale show unsatisfactory results, and alternative questions ought to be tested.